(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article is devoted to the main methodological basis of culturological approach to the linguistic personality formation of agrarian affairs specialists-to be and the methods of its realization in the context of «Ukrainian language according to the vocational guidance» training course.